EFFECT OF SINTERING TEMPERATURE ON TUNGSTEN CARBIDE DENSITIES AND POROSITY - Ade, Ade Saputra; Hidayat, Imam; Prijono, Kusdi; Dimyati, Arbi; Salam, Rohmad; Rohmat, Nur; Suhendi, Suhendi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
The manufacture of tungsten carbide begins with mixing WC with Co in the milling process and then the compaction process is carried out using a compacting machine. After that, the sintering process is carried out to increase the strength of the material. From various studies it was found that the sintering temperature had an effect on the density of the tungsten carbide produced. The problem is what is the best sintering temperature for WC (Tungsten carbide). This study was intended to analyze the effect of temperature on the density and porosity of tungsten carbide. The research was carried out with a compaction press load of 20 tons with 4 variations of sintering temperature and heating electric current strength, namely 50A -600°C, 60A -800°C, 70A -1000°C and 80A -1200°C. The results of this study prove that the WC sintering temperature has a significant effect on density and porosity. The highest average density of 9.4763 g/ml was achieved by specimens with a sintering temperature of 1.000°C and a current of 70A. Microstructural observations using SEM-EDX also proved that this specimen had the best density compared to other specimens.